Multi-Gene Phylogeny of the Ciliate Genus Trachelostyla (Ciliophora, Hypotrichia), With Integrative Description of Two Species, Trachelostyla multinucleata Spec. nov. and T. pediculiformis (Cohn, 1866) - Zhang, Tengyue; Shao, Chen; Zhang, Tengteng; Song, Weibo; Vd’ačný, Peter; Al-Farraj, Saleh A.; Wang, Yurui (Frontiers in Microbiology, 2022)
Many hypotrich genera including Trachelostyla are taxonomically challenging and in a need of integrative revision. Using morphological data, molecular phylogenetic analyses, and ITS2 secondary structures, we attempt to cast more light on species relationships within the marine genus Trachelostyla. The present multi-faceted approach revealed that (1) a large-sized species with numerous macronuclear nodules, isolated from sandy littoral sediments in southern China, is new to science and is endowed here with a name, T. multinucleata spec. nov.; (2) two other Chinese populations previously identified as T. pediculiformis represent undescribed species; (3) multi-gene phylogeny is more robust than single-gene trees, statistically strongly supporting monophyly of the genus Trachelostyla. ITS2 secondary structures and the presence of compensatory base changes in helices A and B indicate the presence of four distinct taxa within the molecularly studied members of the genus Trachelostyla. Molecular data are more suitable for delimitation of Trachelostyla species than morphological characters, as interspecific pairwise genetic distances of 18S, ITS1-5.8S-ITS2, and 28S rDNA sequences do not overlap, while ranges of multiple morphometric features might transcend species boundaries.